UJI EFEK TOKSISITAS TEPUNG SINGKONG PAHIT HASIL DETOKSIFIKASI PADA HEWAN PERCOBAAN - Suryana Purawisastra; Erwin Affandi; Almasyhuri Almasyhuri; Rossi R. Apriyanto (Persagi, 1998)
Toxicity test of detoxified bitter cassava flour was carried old on experimental rats. The objective of the test was to observe the direct effect of the flour on the rats. There were 4 kinds of detoxified flour derived from different varieties of bitter cassava having different cyanide concentrations. The varieties were 46.8, Adira II, Adira IV, and 39.1.1. In the test maize flour and sweet cassava flour were used as controls. It was observed that there was no significant difference in the growth of rats given control flours or detoxified cassava flour. Differences were found in amounts of flours consumed, body weight, and the weights of important organs, heart, liver and kidney. The differences were not related to the cyanide contents in the detoxified cassava flours.Keywords: toxicity test, detoxified bitter cassava flour, cyanide, experimental rats